Red and blue emissions of europium doped gadolinium silicate from porous silica matrix and hydroxide carbonate with spherical shaped particles - Sigoli, F. A.; Davolos, Marian Rosaly [UNESP]; Jafelicci, M. (Elsevier B.V., 2002)
In this work, Eu(III) and Eu(II) doped gadolinium silicates has been obtained as compact tubes starting from spherical gadolinium hydroxide carbonate using the pores of silica matrix as support and its surface as reagent. Eu(III) doped gadolinium silicate with hexagonal phase shows an interesting visible shifted charge transfer band when compared to disilicate with orthorhombic phase that was also obtained. Eu(II) gadolinium silicate has been prepared using CO atmosphere presenting an intense blue emission. The divalent europium system shows a potential application as an UV-blue converter. The samples were characterized by scanning electron microscopy (SEM), X-ray powder diffractometry (XRD) and photoluminescence spectroscopy. (C) 2002 Elsevier B.V. B.V. All rights reserved.
Keywords: porous inorganic support; europium; silicate and luminescence